The roles of hierarchical administrations of tourism governance in China: a content analysis. Issue 2 (4th May 2019) - Marafa, Lawal M.; Qi, Huan; Chan, Chung-Shing
ABSTRACT: Tourism policy and development in China is both administered by its highly hierarchical government structure, which has been argued as a well-established process of policymaking and criticized as the major top-down constraint in policy implementation. This paper analyzed this hierarchical perspective of the Chinese tourism authorities through a content analysis of the official administration documents. The ROSTCM software identified and calculated the frequency of keywords and their associated networks in the regional and local levels. The results are the verbs describing the major role of these levels of government in tourism development which can hopefully be emulated in some countries where tourism development is planned. China National Tourism Administration (CNTA) is at the top of tourism policy and development with clearly defined functions of coordination, policymaking, planning, regulation, investment stimulation, promotion and organization. The decision-making process goes down to regional and local levels with partly different and partly overlapped functions. Regional governments undertake an intermediary role of interpreting national policies and directing these top-down ideas to the local governments that are the last level of administration that delivers and implements the directed policies to the locality. This hierarchical tourism administration implies the threat of misinterpretations between levels of governments. Local-level administrations should be empowered to engage in policymaking as they have closer connection and richer knowledge about local destinations and tourism stakeholders.